Inhibitory Potential of Five Traditionally Used Native Antidiabetic Medicinal Plants on α-Amylase, α-Glucosidase, Glucose Entrapment, and Amylolysis Kinetics In Vitro - Carene M. N. Picot; A. Hussein Subratty; M. Fawzi Mahomoodally (Advances in Pharmacological Sciences)
Five traditionally used antidiabetic native medicinal plants of Mauritius, namely, Stillingia lineata (SL), Faujasiopsis flexuosa (FF), Erythroxylum laurifolium (EL), Elaeodendron orientale (EO), and Antidesma madagascariensis (AM), were studied for possible α-amylase and α-glucosidase inhibitory property, glucose entrapment, and amylolysis kinetics in vitro. Only methanolic extracts of EL, EO, and AM (7472.92±5.99, 1745.58±31.66, and 2222.96±13.69 μg/mL, resp.) were found to significantly (P<0.05) inhibit α-amylase and were comparable to acarbose. EL, EO, AM, and SL extracts (5000 μg/mL) were found to significantly (P<0.05) inhibit α-glucosidase (between 87.41±3.31 and 96.87±1.37% inhibition). Enzyme kinetic studies showed an uncompetitive and mixed type of inhibition. Extracts showed significant (P<0.05) glucose entrapment capacities (8 to 29% glucose diffusion retardation index (GDRI)), with SL being more active (29% GDRI) and showing concentration-dependent activity (29, 26, 21, 14, and 5%, resp.). Amylolysis kinetic studies showed that methanolic extracts were more potent inhibitors of α-amylase compared to aqueous extracts and possessed glucose entrapment properties. Our findings tend to provide justification for the hypoglycaemic action of these medicinal plants which has opened novel avenues for the development of new phytopharmaceuticals geared towards diabetes management.